Efeitos da aplicação de resíduos industriais nas propriedades químicas e biológicas do solo - Cova, Alide Mitsue Watanabe (2012)
The disposal of industrial waste is one of the major problems in the world and, in the search for sustainable alternatives have been evaluated the possibility of applying these in agriculture. To evaluate the potential use of industrial waste inorganic and organic in agricultural soils were carried out two studies. The first to assess the behavior of microbial activity and mineralization of soil C with incorporation of industrial waste and second, to assess changes in soil properties after the addition of industrial waste. It was used for both experiments the completely randomized design, with treatments at first a 3 x 2 x 16 factorial, referring to three doses of inorganic waste (RI): 0, 2,5 and 5,0 Mg ha-1 and two doses organic waste (RO): absence and presence in terms divided into 16 times (3, 6, 9, 12, 15, 21, 28, 35, 42, 49, 56, 63, 70, 77, 84 and 91 days) after initiation of incorporation of treatments and 4 replicates. The amount of organic waste was applied in amounts equivalent to 100 kg N ha-1 (approximately 20 Mg ha-1 of organic waste). The second, in factorial 3 x 2 x 4 using three doses RI: 0, 2.5 and 5.0 Mg ha-1 in the presence and absence of RO applied in quantities equivalent to 100 kg N ha-1, evaluated at 0, 30, 60 and 90 days after incubation with four replications. The addition of RI did not alter soil microbial activity, however being affected by adding the RO. The organic waste showed high recalcitrance. In chemical properties, the incorporation of both residues increased the pH of the soil in the initial phase, but decreased during the study period. The addition of RI increased values of CE, the levels of P, Na, Fe, Cu and Mn at the doses studied and the presence of RO levels N, K and Zn.